Dynamically substructured testing of railway pantograph/catenary systems. (May 2019) - Kobayashi, Shigeyuki; Stoten, David P; Yamashita, Yoshitaka; Usuda, Takayuki
This paper presents a methodology for testing railway pantograph/catenary systems based upon the dynamically substructured system approach for combined physical and numerical components, originally developed by Stoten and Hyde. The main advantage of the dynamically substructured system is that it can provide more stable substructured testing than alternative schemes, such as the commonly used hybrid simulation method, often referred to as hardware-in-the-loop simulation. The developed method is validated through experiments using a simple pantograph rig, together with a numerical simulation of the catenary. In order to realise a real-time simulation of the large catenary model, for the first time in dynamically substructured system testing this study uses (i) a modal analysis technique to reduce the dimension of the contact wire model and (ii) a moving window approach to represent long-distance travel of the pantograph. Finally, the experimental dynamically substructured system test results are compared with simulations of the benchmark pantograph/catenary emulated system.